"Decentralize or Else": Russia's Use of Offensive Coercive Diplomacy against Ukraine. (June 2020) - Alim, Eray
Drawing on the concept of offensive coercive diplomacy, this article examines Russia's strategy in the conflict in Eastern Ukraine and addresses the question of why Russia has failed to achieve its objectives. Through an analysis of notions such as "status quo" (in terms of who overturned it) and international law (in terms of who violated it), I attempt to show that Russia's actions in Eastern Ukraine qualify as offensive coercion. Backed up by force, Russia demanded that Ukraine implement a decentralization process and grant a part of Eastern Ukraine (Donbas) special status. Knowing that Russia's aim is to use Donbas as an instrument to control its political future, Ukraine refused to acquiesce to Russia's demand without restoring its sovereignty in Eastern Ukraine. With both sides refusing to budge, the crisis turned into a zero-sum game. This article seeks to contribute to research on coercive diplomacy by focusing on offensive coercion.